2023
DOI: 10.3389/fimmu.2023.1172242
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of serplulimab plus chemotherapy in the first-line treatment for PD-L1-positive esophageal squamous cell carcinoma in China

Abstract: ObjectiveThe ASTRUM-007 trial (NCT03958890) demonstrated that serplulimab plus chemotherapy administered every 2-week significantly improved progression-free and overall survival in patients with previously untreated, programmed death-ligand 1 (PD-L1) positive advanced esophageal squamous-cell carcinoma (ESCC). This study was aimed to investigate the cost-effectiveness of serplulimab plus chemotherapy in the first-line treatment of PD-L1-positive advanced ESCC.MethodsA partitioned survival model with a 2-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The economics of PD-1 inhibitors for OSCC treatment are also receiving increasing attention. Several cost-effective results of PD-1 inhibitors combined with chemotherapy in OSCC treatment have been published [8,23,[31][32][33][34][35][36][37][38][39][40]. A cost-effectiveness analysis was conducted to compare different PD-1 inhibitors in combination with chemotherapy for the firstline treatment of advanced OSCC in China [8].…”
Section: Discussionmentioning
confidence: 99%
“…The economics of PD-1 inhibitors for OSCC treatment are also receiving increasing attention. Several cost-effective results of PD-1 inhibitors combined with chemotherapy in OSCC treatment have been published [8,23,[31][32][33][34][35][36][37][38][39][40]. A cost-effectiveness analysis was conducted to compare different PD-1 inhibitors in combination with chemotherapy for the firstline treatment of advanced OSCC in China [8].…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the dosages of chemotherapies, the default body weight of 65.0 kg and body surface area of 1.72 m 2 were assumed for Chinese patients. 45 Health state utilities associated with OSCC were unavailable in the included trials; thus, we used those from the RAINBOW trial considering their comparability. 46 The disutility values incurred for treatment-related AEs were obtained from the literature.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, with ICER between $333,199 to $670,309.66 per QALY, the cost-effectiveness of atezolizumab, also a first-line treatment for LSCC, has been negated by both US and Chinese studies, and price reductions have been suggested [ 36 38 ]. Most of the published reviews in this area have targeted patients with non-small cell lung cancer [ 28 ] and have focused on a specific region [ 39 ] or comparison of two specific therapies [ 40 ]. Therefore, no studies have simultaneously compared the cost-effectiveness of all the immunotherapies in patients with LSCC.…”
Section: Introductionmentioning
confidence: 99%